Base concepts of problem of professional development of specialists preschool educational establishments in the field of educationally-health activity - Makovetskaya N.V (Kharkov National Pedagogical University, 2012)
It is found out approaches interpretation of base concepts of research of the system of professional development of specialists of preschool industry of education. Predetermines approaches effective organization by them to educational and health activity. It is formulated author's determinations of concepts professional development, specialist of preschool educational establishment, education and health. It is proved that professional development is a continuous process which foresees the professional studies of specialists. It is certain that to this category educators and instructors belong on a physical culture. It is set that their professional activity must be directed on forming for the under-fives of pictures of healthy way of life. It is found out that stimulant and a motivational component is foreseen by stimulation, their aspiring, teachers of cognitive interests of children to the healthy way of life.